INTRODUCING NEW ASPECTS OF BEAUTY TO GENERATION Z WOMEN: CASE STUDY OF WARDAH BEAUTY PRODUCTS VISUAL ADVERTISING - AA, 1Khoirus Sa adah; Agristi, Elfrida Diva; Nisa, Mir Atun; Susanto, Putu Chris; Dewi, Putu Chrisma (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTVisual advertising in the form of video commercials is one of the most influential means of promotion,because its reach is very broad. Many product advertisers want to convey a message to their viewers tobe the center of attention, one of which is Wardah beauty products. A product that uses the "halal" labeland often includes religious elements such as Muslim models. Wardah cosmetic products try to conveya message to viewers about beauty through Wardah advertisement that women can have an impact andbenefit in all aspects of life ranging from the environment, social, to others, even the world. This articlediscusses the effects of visual advertising from the Wardah brand of cosmetic products on Indonesianwomen, particularly Generation Z women. The study used a descriptive qualitative approach by usingvisual analysis on the video advertising and interviewing targeted participants from five IndonesianGeneration Z women and then comparing, combining, conceptualizing and drawing conclusions fromthe interview results using SWOT analysis approach. The study found that Wardah â€œBeauty MovesYouâ€ advertising campaign introduced new aspects of beauty for women that put forward the values ofprogressive, modern, modesty, courage, and usefulnessâ€”which are found to be favorable from theperspectives of the studyâ€™s Generation Z women participants.Keywords: visual advertising, beauty product, visual analysis, Generation Z, Indonesian womenABSTRAKIklan visual adalah bentuk promosi berbentuk video yang merupakan salah satu upaya pemasaran yangberpengaruh karena dapat menjangkau pangsa pasar yang luas. Banyak upaya pemasaran dilakukanuntuk menyampaikan pesan kepada para penonton untuk menarik perhatian, salah satunya adalahvideo promosi oleh produk kecantikan Wardah. Lini produk ini merupakan produk berlabel â€œhalalâ€yang mengikutsertakan elemen religious seperti model Mulsimah yang berhijab. Produk kosmetikmerek Wardah melalui kampanye â€œBeauty Moves Youâ€ berupaya menyampaikan pesan pemasaranbahwa perempuan dapat memberi dampak bermakna dalam berbagai aspek kehidupan, baik dari sisibisnis, sosial kemasyarakatan, lingkungan, dan sebagainya. Artikel ini mengeksplorasi dampak iklanvisual produk kosmetik merek Wardah terhadap perempuan Indonesia, khususnya Generasi Z.Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis visual dan teknik wawancaraterhadap lima perempuan Indonesia dari Generasi Z, kemudian membandingkan, mengkombinasikan,mengkonsep, dan menyimpulkan hasil wawancara tersebut dengan pendekatan analisis SWOT.Penelitian ini menemukan bahwa kampanye visual Wardah â€œBeauty Moves Youâ€ memperkenalkanaspek baru terkait kecantikan perempuan yang mengedepankan nilai progresif, modern,kesederhanaan, keberanian, dan kebermanfaatanâ€”yang dinilai positif oleh perempuan generasi Z.Kata kunci: iklan visual, produk kecantikan, analisis visual, Generasi Z, perempuan Indonesia